Management of Sleep Disorders in Children With Neurodevelopmental Disorders: A Review. Issue 1 (January 2016) - Blackmer, Allison Beck; Feinstein, James A.
Abstract : Neurodevelopmental disorders (NDDs) are defined as a group of disorders caused by changes in early brain development, resulting in behavioral and cognitive alterations in sensory and motor systems, speech, and language. NDDs affect approximately 1–2% of the general population. Up to 80% of children with NDDs are reported to have disrupted sleep; subsequent deleterious effects on daytime behaviors, cognition, growth, and overall development of the child are commonly reported. Examples of NDDs discussed in this review include autism spectrum disorder, cerebral palsy, Rett syndrome, Angelman syndrome, Williams syndrome, and Smith‐Magenis syndrome. The etiology of sleep disorders in children with NDDs is largely heterogeneous and disease specific. The diagnosis and management of sleep disorders in this population are complex, and little high‐quality data exist to guide a consistent approach to therapy. Managing sleep disorders in children with NDDs is critical both for the child and for the family but is often frustrating due to the refractory nature of the problem. Sleep hygiene must be implemented as first‐line therapy; if sleep hygiene alone fails, it should be combined with pharmacologic management. The available evidence for the use of common pharmacologic interventions, such as iron supplementation and melatonin, as well as less common interventions, such as melatonin receptor agonists, clonidine, gabapentin, hypnotics, trazodone, and atypical antipsychotics is reviewed. Further, parents and caregivers should be provided with appropriate education on the nature of the sleep disorders and the expectation for modest pharmacologic benefit, at best. Additional data from well‐designed trials in children with NDDs are desperately needed to gain a better understanding of sleep pharmacotherapy including efficacy and safety implications. Until then, clinicians must rely on the limited available data, as well as clinical expertise, when managing sleep disorders in the population of children with NDDs.